Exploring the properties of MTO4 compounds using high‐pressure powder x‐ray diffraction. Issue 9 (3rd May 2015) - Errandonea, Daniel
Abstract : In this article it is described how the crystal structure of different technological oxides is modified under compression. Several examples are described and discussed to show how the combined used of synchrotron powder x‐ray diffraction and the diamond‐anvil cell technique allow to understand their high‐pressure behaviour and mechanical properties. The described results contribute to improve the knowledge of the physical properties of tungstates, vanadates, and other materials. Abstract : Several ternary oxides with industrial applications, but also interesting for basic research, have been studied recently at room temperature under high‐pressure conditions using synchrotron powder x‐ray diffraction. In this article, part of these experiments will be summarized. The studied materials include zircon‐type vanadates and scheelite‐type tungstates as well as other oxides related to them. Several pressure‐induced structural phase transitions that take place in these compounds under compression will be here described. In addition, the determination of the crystal structure of the high‐pressure phases will be discussed. The reported studies have also allowed the accurate determination of the axial and bulk compressibility of the studied materials. The influence of experimental conditions on the reported results will be finally commented.